Measurement of Ground Resistance at Syowa Station in the Winter of 1970 (Reports of the Japanese Antarctic Research Expedition) - Masaru AYUKAWA; Shigeo ASHIDA; Hiroji ITO (National Institute of Polar Research, 1971)
The rocket launching facilities were constructed at Syowa Station (69°00'S, 39°36'E), Antarctica, in January 1970. For operating the rocket launching with safety, it is necessary to maintain a good ground even during the winter season. In order to investigate the seasonal variation of ground resistance the measurements of the earth-plate resistance and the ground temperature at 50cm were carried out once in ten days from February 1970 to February 1971. The ground resistance measured at throe sites showed the increase with lowering of the ground temperature : the minimum being 8.4Ω (at 0℃) and the maximum 280.0Ω (-14.5℃) in the rocket ignition system the minimum 5.4Ω (1.0℃) and the maximum 150.0Ω (-12.0℃) in the rocket radar-telemeter system the minimum of 21.0Ω (1.5℃) and the maximum 390.0Ω (-20.4℃) in the radio station system.